Interesting supergene Pb-rich mineral association from the Rovnost mining field, Jachymov (St. Joachimsthal), Czech Republic - Sejkora,J.; Plasil,J.; Cisarova,I.; Skoda,R.; Hlousek,J.; Veselovsky,F.; Jebava,I. (Journal of Geosciences, 2011)
Rich supergene mineral association with prevalence of Pb was found in a shallow gallery of the Rovnost mine, the Jachymov (St. Joachimsthal) ore district, western Bohemia (Czech Republic). Mimetite occurs as colourless transparent flexible fibres of up to 1 mm in length and up to 10 μm in diameter. The fibres form greyish white aggregates (up to 1 cm2 in area) grown on the surface of gangue strongly affected by supergene alteration. The results of the single crystal X-ray diffraction study of mimetite with R1 = 0.0381 are fully consistent with data reported previously for this mineral phase. According to electron microprobe study, interesting are namely elevated contents of SiO4 (up to 0.16 apfu). Among the supergene minerals, cerussite, anglesite, wulfenite, philipsbornite-segnitite minerals, pyromorphite and metazeunerite were determined based on powder X-ray diffraction and electron microprobe analysis. The presence of U (˜ 4 wt. % UO3) and As (up to 4 wt. % As2O5) in wulfenite is particularly noteworthy. Characteristic of the studied mineral association are elevated and omnipresent contents of F-. This mineral assemblage is considered to be a result of a long-term in-situ weathering in near-surface conditions.
Keywords: supergene mineralization; mimetite; lead minerals; Jachymov; Czech Republic